MOLECULAR GENETIC MARKERS FOR DIAGNOSING METACHRONOUS ONCOGYNECOLOGICAL TUMORS IN BREAST CANCER PATIENTS - Izrailbekova K.Sh; Kamishov S.V; Qobilov O.R; Niyozova Sh.Kh; Ubaydullaeva M.J (Western European Studies, 2026)
Breast cancer (BC) patients face an increased risk of developing multiple primary malignant tumors, particularly metachronous oncogynecological neoplasms. Early detection and risk stratification of these secondary malignancies are critical for improving patient outcomes.
Keywords: breast cancer; metachronous tumors; molecular genetic markers